Risk of second malignant neoplasms after cyclophosphamide-based chemotherapy with or without radiotherapy for non-Hodgkin lymphoma. Issue 7 (July 2013) - Xu, Yuanlin; Wang, Huaqing; Zhou, Shiyong; Yu, Man; Wang, Xianhuo; Fu, Kai; Qian, Zhengzi; Zhang, Huilai; Qiu, Lihua; Liu, Xianming; Wang, Ping
Abstract: Relatively little information is available on quantitative risks of therapy-induced second malignant neoplasm (SMN) in patients with non-Hodgkin lymphoma (NHL). A nested case–control study was conducted in a cohort of 3412 patients treated for NHL between 1990 and 2006, including 118 patients with SMN and 472 controls. Risks of leukemia/lung/breast/colorectal and bladder cancer were higher in NHL compared with the general population. A higher risk of leukemia was restricted to patients given a cumulative dose of cyclophosphamide more than 11 250 mg/m 2 . However, no significant association was found between SMN risk with rituximab, fludarabine, anthracyclines, epipodophyllotoxins and platinum, respectively. In combined modality treatment, involved-ﬁeld radiation therapy (IFRT) had a higher risk for second solid cancers as compared to involved-nodal radiation therapy (INRT). For patients receiving radiation doses exceeding 40 Gy, the risk of lung cancer and breast cancer was increased. In conclusion, we found that cyclophosphamide-based therapy increased the risk of SMN in NHL. Leukemia risk was linked with high-dose cyclophosphamide. A received larger radiation field or higher radiation dose also could be an important risk factor for the development of SMN.